PENDIDIKAN KARAKTER MELALUI PEMBELAJARAN MUSIK LOKAL TRADISIONAL GONDANG OGUONG PADA ANAK-ANAK OLEH SALMAN AZIS - Reizki Habibullah; Sigit Purwanto; Nora Putri Sofyan (Institut Seni Indonesia Surakarta, 2023)
This research aims to uncover how Salman Azis teaches the local-traditional music Gondang Oguong, not just as practical training but also as an effort to instill education for character-building values, particularly within the cultural context of Malay in Kampar, to his students. The focus of this research is on the character education values embedded in the Gondang Oguong performance and how Salman Azis carries out the process of instilling these values. To gather information related to these issues, this research employs an ethnographic approach and draws upon the theory of character construction in music education. The results of this research are expected to provide insights and serve as a reference for the development of character education methods through local-traditional music instruction.